The Ice Breaking Model in Early Childhood Education: Training Kindergarten Teachers in Indonesia - HMS, Deden; Rizqina, Aulia Laily (AlBanna: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
Artikel ini bertujuan untuk mengimplementasikan dan mengembangkan model ice breaking pada guru pendidikan anak usia dini di Indonesia melalui pendekatan Participatory Action Research (PAR). Pelatihan dilaksanakan di tujuh provinsi yang dilaksanakan di 18 Kabupaten atau Kota pada periode Mei hingga Juni 2025. Dalam melaksanakan penelitian ini, peneliti memberikan instruksi kepada guru dalam merancang dan mempraktikkan ice breaking seperti, lagu anak, permainan, dan aktivitas pembelajaran menyenangkan yang dapat diterapkan di kelas. Pelatihan dilaksanakan dengan pendekatan Gurame (Guru Asyik, dan Menyenangkan) dan dilengkapi dengan panduan buku dan praktik langsung oleh guru.  Hasilnya menunjukkan guru sangat antusias, merasa lebih percaya diri, dan mampu menyesuaikan ice breaking dengan karakteristik anak usia dini. Peneliti juga menerapkan konsep 4F (Fun, Friendly, Focus, Fresh) dan konsep guru betulan dan kebetulan sebagai refleksi peran profesional guru pendidikan anak usia dini. This article aims to implement and develop an ice breaking model for early childhood education teachers in Indonesia through the Participatory Action Research (PAR) approach. The training was conducted in seven provinces across 18 regencies or cities during the period of May to June 2025. In this study, the researcher provided instructions to teachers on designing and practicing ice breaking activities such as children’s songs, games, and enjoyable learning activities that can be applied in the classroom. The training was carried out using the Gurame approach (which stands for Guru Asyik dan Menyenangkan or Fun and Enjoyable Teachers) and was supported by a training manual and direct practice sessions by the teachers. The results showed that teachers were highly enthusiastic, felt more confident, and were able to adapt ice breaking activities to the characteristics of young children. The researcher also applied the 4F concept (Fun, Friendly, Focus, and Fresh) and introduced the concept of guru betulan (genuine teacher, a teacher who teaches with full responsibility, dedication, and continuous self-development) and guru kebetulan (accidental teacher, a teacher who teaches merely as a routine without true commitment or creativity) as a reflection of the professional role of early childhood education teachers.